2019
DOI: 10.9734/sajrm/2019/v4i330110
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Physicochemical and Bacteriological Quality of Public Swimming Pool in Selected Hotels in Ado-Ekiti, Nigeria

Abstract: The physicochemical and bacteriological assessment of pool water samples from selected hotels in Ado-Ekiti, Nigeria was investigated. A total of 10 pool water samples were collected from five pools before and after use following standard procedures. Physicochemical and bacteriological analyses were performed using standard methods. Antibiotic sensitivity testing was carried out according to CLSI procedures. Physicochemical analyses showed that the pool water samples were clear and colourless. The different par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Although, this agreed with the studies of Onifade, et al [9], Ajadi, et al [10], and Yedeme, et al [11]. On the other hand, it was not in agreement with the studies of Clark, et al [12], Edimeh, et al [13], and Onifade, et al [14]. High temperature values have been attributed to the prevailing weather condition [14,15].…”
Section: Temperatures Of the Swimming Poolsmentioning
confidence: 52%
“…Although, this agreed with the studies of Onifade, et al [9], Ajadi, et al [10], and Yedeme, et al [11]. On the other hand, it was not in agreement with the studies of Clark, et al [12], Edimeh, et al [13], and Onifade, et al [14]. High temperature values have been attributed to the prevailing weather condition [14,15].…”
Section: Temperatures Of the Swimming Poolsmentioning
confidence: 52%
“…Helena Haven Hotel Swimming Pool (HHHSP) had no bacterial growth, which could be as a result of treatment of the swimming pool before collection of the sample. Onifade et al, (2019) in their studies also reported that the total bacteria, coliform and Escherichia coli counts of pool water samples were higher after use than before use. The organisms identified are Staphylococcus epidermidis, Staphylococcus aureus, Klebsiella and Micrococcus species.…”
Section: Resultsmentioning
confidence: 89%
“…and Staphylococcus aureus 2 (5%). Similarly, Onifade et al, (2019) also identified Escherichia coli (66.7%), Enterococcus faecalis (23.8%)and Pseudomonas aeruginosa(9.5%), while analyzing the bacteriological quality of public swimming pools in selected hotels in Ado-Ekiti, Nigeria. These different organisms continue to grow and multiplys uch that their population increases to a density that could result in illnesses like cutaneous, gastrointestinal or respiratory tract diseases in the users (Santhini et al, 2018).…”
Section: Issn: 2319-7706 Volume 9 Number 6 (2020)mentioning
confidence: 99%
“…More so, notably infected persons with skin infections as well as life-threatening diseases caused by these pathogens are not screened out from using the pool (Ajadi and Thonda, 2017). Similarly, C. albicans, a diploid filamentous fungus; is opportunistic in nature indicted in causing oral and genital infection diseases in humans (Ryan and Ray, 2004) invading men using hyphae (Peters et al, 2012;Onifade et al, 2019). The reduced number of isolates after the change of water has exonerated biofilms formations along the pipes as another probable means of contaminating the pool.…”
Section: Discussionmentioning
confidence: 99%